OPTIMALISASI POTENSI PAJAK DAN RETRIBUSI DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KOTA AMBON - Tupamahu, Maria K.; Oppier, Hermi; Rijoly, Jacobus. C.D. (FEB Universitas Sam Ratulangi Manado, 2019)
Since Indonesia implemented regional autonomy, part of the financial authority was delegated to the regions so that the regions could independently optimize their regional financial potential, mainly from taxes and levies as their main source of income. Ambon City as an area that has long implemented autonomy still faces the problem of how to optimize the potential of PAD, especially through taxes and levies. This study aims to analyze strategies for optimizing taxes and levies in Ambon City. This study uses two research instruments, namely SWOT analysis and Model Vector Error Correction Model. Estimated results are then developed by forecasting for the next 10 years. The results show that both taxes and levies experienced a significant increase but in certain periods experienced fluctuations influenced by several macroeconomic variables.